Mitochondrial Genome Resource of Phomopsis longicolla, a Fungus Causing Phomopsis Seed Decay in Soybean - Shuxian Li; Youjin Deng (PhytoFrontiers, 2021)
Phomopsis seed decay is one of the most devastating seed diseases reducing soybean seed quality worldwide. This disease is caused primarily by a seed-borne fungus, Phomopsis longicolla (syn. Diaporthe longicolla). As part of a genome sequencing project for P. longicolla, we present the mitochondrial genome resource of the isolate MSPL 10-6, one of the most aggressive field isolates. The circular mitochondrial genome is 53,646 bp long with GC content of 34.27%, and it encodes 14 common protein genes, 23 tRNA and two rRNA genes, and 10 introns. Forty-five SNPs and InDels also were identified during comparative analyses with another isolate. The mitochondrial genome sequence provides a useful resource for developing molecular markers for pathogen detection and for improvement of control strategies for the disease.[Figure: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.